Nietzsche, all too nietzschean - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
The article is a study of the biography and works of F. Nietzsche. The problematic of distorting his ideas is being raised. Its influence on the philosophy of the 20th century, and feminism in particular, is examined